Effects of Marijuana Use on Prefrontal and Parietal Volumes and Cognition in Emerging Adults - Price, Jenessa S. (Psychopharmacology (Berl), 2015)
RATIONALE: Chronic marijuana (MJ) use among adolescents has been associated with structural and functional abnormalities, particularly in developing regions responsible for higher order cognition. OBJECTIVES: This study investigated prefrontal (PFC) and parietal volumes and executive function in emerging adult MJ users and explored potential gender differences. METHODS: Participants (ages 18–25) were 27 MJ users and 32 controls without neurologic or psychiatric disorders or heavy other drug use. A series of multiple regressions examined whether group status, past year MJ use, and their interactions with gender predicted ROI volumes. Post-hoc analyses consisted of brain-behavior correlations between volumes and cognitive variables and Fisher’s z tests to assess group differences. RESULTS: MJ users demonstrated significantly smaller medial orbitofrontal (mOFC; p=.004, FDR p=.024) and inferior parietal volumes (p=.04, FDR p=.12); follow-up regressions found that increased past year MJ use did not significantly dose-dependently predict smaller mOFC volume in a sub-sample of individuals with at least one past year MJ use. There were no significant gender interactions. There was a significant brain-behavior difference by group, such that smaller mOFC volumes were associated with poorer complex attention for MJ users (p<.05). CONCLUSIONS: Smaller mOFC volumes among MJ users suggest disruption of typical neurodevelopmental processes associated with regular MJ use for both genders. These results highlight the need for longitudinal, multi-modal imaging studies providing clearer information on timing of neurodevelopmental processes and neurocognitive impacts of youth MJ initiation.